2022
DOI: 10.3390/v14102150
|View full text |Cite
|
Sign up to set email alerts
|

A Transcriptomics-Based Bioinformatics Approach for Identification and In Vitro Screening of FDA-Approved Drugs for Repurposing against Dengue Virus-2

Abstract: The rising incidence of dengue virus (DENV) infections in the tropical and sub-tropical regions of the world emphasizes the need to identify effective therapeutic drugs against the disease. Repurposing of drugs has emerged as a novel concept to combat pathogens. In this study, we employed a transcriptomics-based bioinformatics approach for drug identification against DENV. Gene expression omnibus datasets from patients with different grades of dengue disease severity and healthy controls were used to identify … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 91 publications
0
7
0
Order By: Relevance
“…Among the drugs which showed anti CHIKV activity in the present study, resveratrol, doxorubicin, lomibuvir and enalaprilat were also reported to exert anti-DENV activity ( Punekar et al., 2022 ). These drugs might be useful in regions where both viruses are endemic and need to be prioritized.…”
Section: Discussionmentioning
confidence: 71%
See 4 more Smart Citations
“…Among the drugs which showed anti CHIKV activity in the present study, resveratrol, doxorubicin, lomibuvir and enalaprilat were also reported to exert anti-DENV activity ( Punekar et al., 2022 ). These drugs might be useful in regions where both viruses are endemic and need to be prioritized.…”
Section: Discussionmentioning
confidence: 71%
“…Towards the search to discover newer CHIK viral targets and mechanisms for the development of novel antivirals, in the present study, we investigated the anti-CHIKV activity of fourteen FDA-approved drugs. Some of these drugs were identified as potential drug candidates against dengue, another mosquito-borne disease ( Punekar et al., 2022 ) which mimics CHIKF in symptoms ( Table 3 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations